Parental work absenteeism is associated with increased symptom complaints and school absence in adolescent children - Mari Hysing; Keith J. Petrie; Tormod Bøe; Børge Sivertsen (BMC, 2017)
Abstract Background Previous studies have proposed that having parents out of work may influence adolescent illness behaviour and school attendance. However, prior research investigating this question has been limited by retrospective reporting and case control studies. In a large epidemiological study we investigated whether parental work absence was associated with symptom complaints and increased school absenteeism in adolescents. Methods We analysed data from a large epidemiological study of 10,243 Norwegian adolescents aged 16-19. Participants completed survey at school, which included demographic data, parental work absence and current health complaints. An official registry provided school attendance data. Results Parental work absence was significantly related to the number of adolescent symptom complaints as well as school absenteeism. Having a father out of work was associated with an increased likelihood of being in the highest quartile of symptom reporting by an odds-ratio of 2.2 and mother by 1.6 (compared to the lowest quartile). Similarly, parental work absenteeism was associated with an increased likelihood of being in the highest quartile for school absence by an odds-ratio of 1.9 for a father being out of work and 1.5 for a mother out of work. We found that the number of adolescent symptom complaints mediated the relationship between parental work absenteeism and school absenteeism. Conclusion We found that parental work absence was significantly associated with the number of adolescent symptom complaints and school absenteeism. The results suggest that parents may play a critical modelling role in the intergenerational transmission of illness and disability behaviour.